The relationship between motoric dominance and functional dominance while executing judo techniques: a study on laterality - Dopico, X.; Iglesias-Soler, E.; Carballeira, E.; Mayo, X.; Ardá, A.; González-Freire, M. (Archives of Budo, 2014)
Background and Study Aim: Motoric Dominance is defined as the preferential use of an upper or lower limb in a variety of common tasks, while the term Functional Dominance refers to laterality evidenced by performing different specialised sport techniques. The main purposes of this study were knowledge about the relations between motoric dominance and functional dominance in a group of high-level Spanish judokas significantly diversified in terms of the age and the training experience. We solve the three research tasks: 1) to assess laterality of hand, foot/leg and preference in turning (i.e., motoric dominance); 2) to assess the preferences (right-dominant, left-dominant, or symmetrical) while executing three specific judo techniques (uchi mata, seoi nage and o soto gari) (i.e. functional dominance); 3) to analyse the relationship between motoric dominance and functional dominance. Material and Methods: The sample was composed of 64 high-level Spanish judokas (39 males and 25 females). Their average age and training experience were 19.5 years (range 16-28) and 10.3 years (range 7-18), respectively. Besides descriptive statistics (percentages of motoric and functional dominance), the categorical data were analysed with a Pearson chi square (p-value = 0.05); when the relation was significant the adjusted residuals were also analysed. The strength of association was calculated with the corrected contingency coefficient (Ccorr). Results: Motoric dominance for hand was 7.8% (left-handers), for foot/leg 15.6% (left-footers) and preference in turning was 23.4% (left-turn). The analysis of functional dominance showed that the vast majority of the observed judokas presented right dominance (66-86%) for executing specific judo techniques. Finally, no relationship (p > 0.05) was detected in 8 out of 9 evaluated associations between motoric and functional dominance. We only found an association (p = 0.027) between motoric dominance of turn and execution of o soto gari. Conclusion: These results suggest that laterality expressed as functional dominance is likely to be acquired through specific practice of judo motor skills.